El juego y la motricidad gruesa en los niños de 4 a 5 años de la escuela de educación básica 18 de Noviembre ubicada en la ciudad de Loja, en el período 2019-2020 - Sisalima Granda, Liseth Alejandra (2021)
The present research which title is THE GAME AND THICK MOTOR SKILL IN CHILDREN FROM 4 TO 5 YEARS OLD FROM THE 18 DE NOVIEMBRE BASIC EDUCATION SCHOOL LOCATED IN THE CITY OF LOJA, DURING THE PERIOD 2019-2020 had as a general objective to analyze the importance of games in thick motor skill in children from 4 to 5 years old. The researching design used was non-experimental, furthermore the approach was mixed allowing to investigate, collect, analyze and link qualitative and quantitative data to get the planned objective. The methods used were descriptive, analytical - synthetic and inductive-deductive that helped to carry out this research. The diagnose was done using a study sample of 20 people: 19 children and a teacher. The technique used was an interview to the teacher and the instrument was the Abbreviated Development Scale (ADS-1) of Nelson Ortiz to children, which showed that 63% of the studied population have problems in the thick motor skill due to their development is in the medium and it alerts because it reflects difficulties in this area. In conclusion, in view of the fact that the results obtained clearly show a trouble, a proposal for children's games called “playing playing I'm growing” which consists of various games that involve movements of the whole body, which will help enhance their development at a social, emotional and motor level the same that will be delivered to the corresponding authorities for subsequent application. This proposal was not applied due to the health emergency caused by Covid-19 in which the whole world is immersed